Transformasi Kepemimpinan: Pengaruh Kepemimpinan Transformasional Terhadap Pengembangan Karir Karyawan - Mutia, Dini Havid; Siregar, Ayunda Putri Amirah; Mukhalisin, Ahmad (Philosophiamundi, 2024)
Transformational leadership is a major focus in modern organizational dynamics because it inspires and directs individuals toward a shared vision. This research explores transformational leadership's influence on employee career development in di PT BANK MANDIRI (Persero), TBK. This research uses data from various organizations to analyze interactions between leaders and followers, contextual factors, and individual characteristics. The method used includes a qualitative approach to understand the influence of multiple variables on career development. The research results show that transformational leadership, which involves high interaction between leaders and followers, contributes significantly to employee career development. However, successful implementation is highly dependent on in-depth understanding and proper implementation. In conclusion, transformational leadership is effective in developing employee careers, but it must be applied by paying attention to other variables that are also influential.